The influence of innovation practices on human capital development: the mediation role of innovation management - Salih Alhemairy, Zayed Hussain (2022)
Innovation is the pillar of success in almost all industries in the world. The application of innovation become an essential practice for public and government organizations. Today, the development of human capital is not limited to human resources management but can be achieved through innovation management as well. There is a rich of studies in the literature on innovation practices and human capital development. Resources Based View Theory (RBV) explain that human capital is effectively working as intangible resources to an organization. Yet, the literature did present empirical results on the role of RBV in fostering human capital development with the aid of innovation. However, it is still unclear how innovation management influences relationship between innovation practices and human capital development. Therefore, the aim of this study is to examine these relationships, as well as proposing a framework that constructs these three variables. To achieve these objectives, quantitative method has been applied to validate the hypotheses and the model fit of the conceptual framework. The questionnaire has been designed as the main data collection tool for the survey. The population is the staff and employees working and the Ministry of Community Development in United Arab Emirates. From the survey 387 valid questionnaires have been considered for the analysis. The result of this study revealed that innovation practices have a significant effect on human resources development, while innovation management partially mediates this relationship. Hence, it is recommended to focus on main practices of innovations such as product innovation, process innovation, marketing innovation, while setting innovation strategy and innovation culture inside any organization will improve the skills and knowledge of the workforce and foster their ability to deal with the challenges of fast development in workplace technologies. The contribution of this study is adding to the body of knowledge the significant role of innovation management on human capital development in public organization. The conceptual framework could be applied in other countries and not limited to UAE, as well as various industries. The outcome of this model project is not limited to public sector and could be extended to the private organizations as well in future studies.